2023
DOI: 10.2196/49490
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Patient Workload and Its Impact on Outcomes During New Cancer Patient Visits: Analysis of a Convenience Sample

Safa Elkefi,
Onur Asan

Abstract: Background Studies exploring the workload in health care focus on the doctors’ perspectives. The ecology of the health care environment is critical and different for doctors and patients. Objective In this study, we explore the patient workload among newly diagnosed patients with cancer during their first visit and its impact on the patient’s perceptions of the quality of care (their trust in their doctors, their satisfaction with the care visits, their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…To mitigate the risk of bias caused by qualitative research, our study initially used a triangulation design with findings reported in different studies [ 3 ]. For more transparency and accuracy, different participants with different backgrounds reviewed and confirmed the transcripts and interpretations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To mitigate the risk of bias caused by qualitative research, our study initially used a triangulation design with findings reported in different studies [ 3 ]. For more transparency and accuracy, different participants with different backgrounds reviewed and confirmed the transcripts and interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…The initial physician visits after a cancer diagnosis are a critical period in which patients face a range of challenges that can significantly disrupt their lives. Symptoms of the disease and the overwhelming decisions related to treatment can pose a threat to their physical, cognitive, and emotional well-being [ 3 ]. Patients often struggle to comprehend medical information and express frustration with prolonged waiting periods for prognoses and follow-ups [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, self-efficacy is a proximal and direct predictor of health behavior [ 29 , 30 ]. According to social cognitive theory, a personal sense of control facilitates health behavior change [ 31 ].…”
Section: Introductionmentioning
confidence: 99%